Flushing out the scattering: fast on-chip microfluidic clearing of microtissues - Yao, Junjie (Microphysiological Systems, 2017)
By generating three-dimensional microtissues or organoids that better mimic the in vivo cellular functions than the two-dimensional cell cultures, the organ-on-a-chip technologies have been playing an increasingly important role in fundamental biology and drug discovery (1). The fast-growing on-chip microfluidic field is accompanied by the high demand for on-site imaging of the microtissues’ morphology, function, and molecular signatures. Clearly, to image the three-dimensional microtissues, the imaging technique should ideally provide volumetric information, together with microscopic resolutions for cellular or even subcellular analysis (2). Although many imaging modalities possess three-dimensional imaging capability, only optical microscopy, primarily the confocal microscopy and multi-photon microscopy, has the required spatial resolution and molecular/chemical sensitivity, and thus is widely used with on-chip microfluidic systems (3). However, the biological tissues are notoriously unfriendly to photons, with strong optical scattering resulted from the inhomogeneous distribution of subcellular structures, including cell membranes, nuclei, and mitochondria (4). High-resolution optical microscopy often suffers from the strong optical scattering of tissues, leading to a shallow imaging depth of a few hundred micrometers.